2021
DOI: 10.3389/fmars.2021.742209
|View full text |Cite
|
Sign up to set email alerts
|

Kelp in the Eastern Canadian Arctic: Current and Future Predictions of Habitat Suitability and Cover

Abstract: Climate change is transforming marine ecosystems through the expansion and contraction of species’ ranges. Sea ice loss and warming temperatures are expected to expand habitat availability for macroalgae along long stretches of Arctic coastlines. To better understand the current distribution of kelp forests in the Eastern Canadian Arctic, kelps were sampled along the coasts for species identifications and percent cover. The sampling effort was supplemented with occurrence records from global biodiversity datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 121 publications
(185 reference statements)
8
27
0
Order By: Relevance
“…solidungula (Table 1), the latter of which is known to complete much of its annual growth under sea‐ice (Chapman & Lindley, 1981; Dunton & Schell, 1986). The importance of sea‐ice in modelling Arctic kelp distributions is also reported by Goldsmit et al (2021). It can be expected, however, that contemporary marine forests at the highest latitudes are extremely patchy, persisting only where the ebb and flow of sea ice dynamics facilitate a brief growing season, and frequently occurring at low per area biomasses, depth ranges, and cover compared to marine forests at lower latitudes (Filbee‐Dexter et al, In press; Krause‐Jensen et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…solidungula (Table 1), the latter of which is known to complete much of its annual growth under sea‐ice (Chapman & Lindley, 1981; Dunton & Schell, 1986). The importance of sea‐ice in modelling Arctic kelp distributions is also reported by Goldsmit et al (2021). It can be expected, however, that contemporary marine forests at the highest latitudes are extremely patchy, persisting only where the ebb and flow of sea ice dynamics facilitate a brief growing season, and frequently occurring at low per area biomasses, depth ranges, and cover compared to marine forests at lower latitudes (Filbee‐Dexter et al, In press; Krause‐Jensen et al, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, of the environmental variables used to train our models, the presence of sea-ice best predicted the presence of cryophilic species D. socialis and L. solidungula (Table 1), the latter of which is known to complete much of its annual growth under sea-ice (Chapman & Lindley, 1981;Dunton & Schell, 1986). The importance of sea-ice in modelling Arctic kelp distributions is also reported by Goldsmit et al, 2021;Jueterbock et al, 2013Jueterbock et al, , 2016, and similar trends of northward shifts reported in temperate North Atlantic taxa (Westmeijer et al, 2019)…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations